Unlocking New Pharma/Nutraceutical Frontiers With Neuroprotective Properties of Three Hypericum Species: A Study Combination With In Vitro and In Silico Methodologies - Bahsi, Muammer; Di Simone, Simonetta Cristina; Zheleva-Dimitrova, Dimitrina; Zengin, Gokhan; Cusumano, Gaia; Flores, Giancarlo Angeles; Ferrante, Claudio (Wiley, 2025)
This study investigates the phytochemical composition and biopharmacological potential of three Hypericum species (H. scabrum, H. lysimachioides, and H. uniglandulosum) from Turkey. Aqueous and hydroalcoholic extracts were analyzed for their total phenolic content (TPC), total flavonoid content (TFC), and individual components (by the UHPLC-HRMS technique). Antioxidant activities were investigated by DPPH, ABTS, CUPRAC, FRAP, phosphomolybdenum, and metal chelating assays. The inhibition effects of the tested extracts on acetylcholinesterase (AChE), butyrylcholinesterase (BChE), tyrosinase, amylase, and glucosidase were examined. One hundred compounds were identified in the chemical composition, and specific compounds for the genus Hypericum, such as hyperoside, hypericin, and pseudohypericin, were detected. The highest TPC was detected in the ethanol/water extract of H. lysimachioides with 69.21 mg GAE/g. Furthermore, the ethanol/water extract showed the strongest free radical and reducing effect. The ethanol/water extracts of the tested Hypericum species were more active in tyrosinase, amylase, and glucosidase than the water extracts. Neuroprotective assessments indicated downregulation of COX-2 and NOS-2 genes in LPS-stimulated mouse cortex models, alongside modulation of SERT and NET expression, suggesting reduced neuroinflammation and enhanced neurotransmitter release. Molecular docking and dynamics analyses highlighted strong binding interactions, especially in the NET_hyperoside and NET_myricitrin complexes. The results indicate significant therapeutic potential for these extracts, supporting their development as natural agents against oxidative stress, neuroinflammation, and related neurodegenerative diseases.
Keywords: antioxidant; Hypericum; hyperoside; in silico methods; neuromodulator; novel pharmaceutics